2012
DOI: 10.1002/pd.3928
|View full text |Cite
|
Sign up to set email alerts
|

Secondary bladder herniation in isolated gastroschisis justifies increased surveillance

Abstract: Objectives To assess the perinatal outcome of fetuses with gastroschisis complicated by secondary bladder herniation.Population and materials This was a retrospective study of all cases of isolated gastroschisis associated with bladder herniation managed at our institution. Prenatal ultrasound, obstetrical and perinatal information were collected. Pathology reports were also gathered. ResultsOut of 105 cases of gastroschisis managed at our institution, six (5.7%) were associated with secondary bladder herniati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 23 publications
3
13
0
2
Order By: Relevance
“…As would be expected with this mechanism, additional bladder herniation seems to increase the risk of fetal demise (Mousty et al, ), and the frequent finding of an eviscerated bladder (observed in two of our cases) renders further support to our hypothesis that organs herniate through the umbilical ring in GS. The allantois, an extension of the bladder, normally exits through the umbilical ring into the cord and it is unlikely that the bladder would extrude through a hole different from the one containing its extension.…”
Section: Discussionsupporting
confidence: 90%
“…As would be expected with this mechanism, additional bladder herniation seems to increase the risk of fetal demise (Mousty et al, ), and the frequent finding of an eviscerated bladder (observed in two of our cases) renders further support to our hypothesis that organs herniate through the umbilical ring in GS. The allantois, an extension of the bladder, normally exits through the umbilical ring into the cord and it is unlikely that the bladder would extrude through a hole different from the one containing its extension.…”
Section: Discussionsupporting
confidence: 90%
“…The majority of MFM specialists in our study began testing at 32 weeks (68%; 89/131), which is consistent with retrospective reviews in the literature [6-9]. This timing may be secondary to minimal change noted in the bowel until 30–32 weeks, after which time more rapid changes can be seen [20].…”
Section: Discussionsupporting
confidence: 69%
“…Monitoring often begins with monthly ultrasounds until 30–32 weeks of gestation, after which time the frequency of testing increases to either weekly or even biweekly [6-9]. The main forms of testing include Doppler ultrasound of the umbilical artery, biophysical profile (BPP), and nonstress test (NST) [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, bladder herniation is a rare event that seems to be related to fetal distress in our study population. Mousty et al also suggested that fetuses with gastroschisis and bladder herniation should be monitored due to the increased frequency of fetal distress.…”
Section: Discussionmentioning
confidence: 99%